Dispersion stability of hBN Nanoparticle in liquid phase with different dispersion agents / Al Alif Elmi Mohd Nawi...[et al.] - Mohd Nawi, Al Alif Elmi; Chua Abdullah, Muhammad Ilman Hakimi; Abdollah, Mohd Fadzli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Solid nanoparticles nowadays became a new solution to advance additive in lubricant technologies due to its ability to perform without jeopardies the lubricant formulation, but it tends to sediment due to gravitational force. The aim of this study is to investigate the effect of difference surfactant agent for better dispersion of solid nanoparticles inside the liquid phase. A set of nano-oil was prepared according to L9 Taguchi array by using ultrasonic homogenizer. Three types of surfactant agent were used which are sodium cholate, oleic acid and Sodium Benzene Dodecyl Sulphonate (SDBS). The absorbance values of the nano-oils were measured using UV-spectrometer as quantitative results. The sample image of the sedimentation process was recorded as a qualitative result. The result shows that suspension of conventional engine oil SAE 15W-40 with the addition of hBN nanoparticles and surfactant agent of SDBS manage stable over the period of 58 days.